Symbols of Time in Russian Wedding Folklore of Udmurtia - S. V. Tolkacheva (Научный диалог, 2021)
The article is devoted to the study of the system of artistic images of Russian wedding  folklore of the modern Udmurt Republic.  The relevance of the work is due to the fact that the temporal processes of the wedding ritual itself, as well as family-clan  and natural rhythms are first considered on the example of wedding folklore that exists in the territory of the modern republic. Particular attention is paid to the images of heavenly bodies, the kingdom of plants, zooand ornithomorphic   images,   the   symbolism   of sound signals. The sun  is  shown  to  be the central artistic  image  associated  with  the display of time. As a result of the analysis, it was found that  semantically,  the  images of evening dawn, morning dawn and night have significant  similarities.  The  question of the possible division of the night into two time periods is considered — a dark one, which does not correspond to a wedding situation, and a light one,  which  regulates the course of ritual time. It  is  shown  that  the image of the night is a symbol of the first conjugal intercourse. It has been established that the mention of the trumpet and the bell   in the songs emphasizes  the  sacred  status  of the wedding ceremony.  It is  noted  that  in wedding songs, the symbolism of the sound of the bell and trumpet merges with  the symbolism of the sun. It was revealed that in the description of emporal processes there may be categories of morality.